Food Restriction Reveals Individual Differences in Insulin-Like Growth Factor-1 Reaction Norms - Tóth, Zsófia; Mahr, Katharina; Ölveczki, Gyula; Őri, Levente; Lendvai, Ádám Zoltán (Frontiers in Ecology and Evolution, 2022)
Most organisms have to cope with unpredictable environmental changes such as fluctuations in nutritional resources. Insulin-like growth factor-1 (IGF-1) is an evolutionarily conserved hormone that is highly sensitive to the individual nutritional status and regulates major life history traits including lifespan and reproduction across vertebrates. To investigate the role of IGF-1 during periods of food shortages, we alternated two feeding regimes (110% and 70% of daily food intake) after a period of ad libitum feeding in captive bearded reedlings (Panurus biarmicus) and repeated each dietary treatments twice. Birds lost mass under food restriction, but the magnitude of mass change depended on the preceding dietary conditions. Moreover, bearded reedlings showed large, repeatable individual differences in their IGF-1 reaction norms with some individuals increasing IGF-1 levels in response to a restricted diet, whereas others showing no responses or decreased IGF-1 levels. The latter response was explained by differences in average body mass: heavier individuals had higher control IGF-1 levels and were more likely to decrease IGF-1 levels in response to the dietary restriction than did lighter ones. This result uncovers an individual by environment interaction (I×E) and may have important implications for the evolution of IGF-1 related hormonal phenotypes in this species.